2000
DOI: 10.1097/00006534-200003000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Use of Fibrin Glue to Induce Site-Directed Osteogenesis from Cultured Periosteal Cells

Abstract: The purpose of this study was to determine whether a combination of fibrin glue and cultured periosteal cells will result in new bone formation at heterotopic sites in nude mice. Growing cells and developing matrices surrounding periosteal explants from the diaphyses of radii of newborn calves were minced and mixed with fibrin glue in a syringe. The cell/matrix-fibrin glue admixture was then injected into the subcutaneous space on the dorsum of athymic nude mice. After 12 weeks of implantation, gross morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 25 publications
0
61
0
2
Order By: Relevance
“…7c). Insular areas of calcistudies, periosteal cells were cultured in medium supplemented with 50 µg/ml ascorbic acid (19,23). A convenfication were present with von Kossa staining (Fig.…”
Section: Discussion Bone Engineering Using the Bovine Periosteal Cellmentioning
confidence: 99%
See 2 more Smart Citations
“…7c). Insular areas of calcistudies, periosteal cells were cultured in medium supplemented with 50 µg/ml ascorbic acid (19,23). A convenfication were present with von Kossa staining (Fig.…”
Section: Discussion Bone Engineering Using the Bovine Periosteal Cellmentioning
confidence: 99%
“…7c). In 2000, Isogai et al (19) studied fibrin glue/periosteal cell constructs and reported results stripped periosteum can also be effective for bone for- solve problems of bone resorption after implantation.…”
Section: Discussion Bone Engineering Using the Bovine Periosteal Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Periosteal cells have been widely used in bone tissue engineering by isolating osteoprogenitor cells from the patient's periosteum and seeding them into bioresorbable scaffolds [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…They have been used in conjunction with other biomaterials such as coral or hydroxyapatite to heal bone defects [20,21]. It has been demonstrated that fibrin glue can be used as a carrier for calvarial osteoprogenitor cells to repair critical sized osseous facial defects [22] and for periosteal cells to induce heterotropic osteogenesis in rat experiments [23]. It has also been reported that fibrin glue together with periosteum derived osteoprogenitor cells can heal segmental bone defects in rabbits [9].…”
Section: Page 4 Of 35mentioning
confidence: 99%